Government Communication Barriers in Preventing Child Marriage in Jember Regency - Juariyah, Juariyah; Thirofy, Ahda Makhzumi; Parto, Parto (Budapest International Research and Critics University, 2025)
The phenomenon of child marriage has become a frequently heard social problem and is widespread in various regions, including Jember Regency. The researcher aimed to determine a communication strategy to stop child marriage in Jember Regency by the Child Protection and Family Planning Agency (DP3AKB). This research employed qualitative methods through interviews, observation, and documentation. The results indicate that the Government Communications Agency, specifically the Jember Child Protection Department, identified several obstacles to ending child marriage in Jember. These challenges relate to the Jember City Child Protection Agency, particularly its belief in traditional customs, low public understanding, lack of human resources, and limited communication with various stakeholders. Therefore, a culturally based approach or religious leader-based approach is needed, given the community's belief in traditional customs. Volunteers need to be recruited to ensure that more parties are involved in child marriage prevention programs.